Elusive Togetherness : Church Groups Trying to Bridge America's Divisions. - Lichterman, Paul (Princeton University Press, 2011)
Many scholars and citizens alike have counted on civic groups to create broad ties that bind society. Some hope that faith-based civic groups will spread their reach as government retreats. Yet few studies ask how, if at all, civic groups reach out to their wider community. Can religious groups--long central in civic America--create broad, empowering social ties in an unequal, diverse society? Over three years, Paul Lichterman studied nine liberal and conservative Protestant-based volunteering and advocacy projects in a mid-sized American city. He listened as these groups tried to create bridg.